Kinematic analysis of Labrador Retrievers and Rottweilers trotting on a treadmill - Agostinho, F. S. [UNESP]; Rahal, Sheila Canevese [UNESP]; Miqueleto, N. S. M. L. [UNESP]; Verdugo, M. R. [UNESP]; Inamassu, L. R. [UNESP]; El-Warrak, A. O. (Schattauer Gmbh-verlag Medizin Naturwissenschaften, 2011)
Objectives: The purpose of the study was to evaluate kinematic patterns in clinically normal Labrador and Rottweiler dogs trotting on a treadmill at a constant velocity.Methods: Ten Labrador Retrievers aged from 2.2 to 5.1 years, and 10 Rottweilers aged from two to 5.9 years were used. A three-dimensional capture system was used to perform analysis of joint kinematics. Kinematic data were collected by use of a triple-camera system. The kinematic study was performed first on the right side of the dog, and then on the left side. Data were analysed by use of a motion-analysis program. Flexion and extension joint angles, angular velocity and angular acceleration were determined for the shoulder, elbow, carpal, hip, stifle, and tarsal joints.Results: Within each group, the differences between the right and left limbs in all variables were not significant. Significant differences occurred between Labradors and Rottweilers in the following categories: angular displacement and minimum angular acceleration of the stifle (Rottweiler >Labrador); angular displacement and maximum angular velocity of the tarsus (Rottweiler >Labrador); minimum angular velocity of the shoulder (Labrador >Rottweiler); angular displacement, maximum angular acceleration, maximum angular velocity, and minimum angular velocity of the elbow (Labrador>Rottweiler); and maximum angle and maximum angular velocity of the carpus (Labrador>Rottweiler).Clinical significance: Both breeds had similar kinematic patterns, but there were magnitude differences, especially of the elbow and stifle joints. Therefore, each breed should have a specific database.
Keywords: Gait analysis; dog; kinematic